Peculiarities in the panoramic radiograph of patients with secondary hyperparathyroidism due to terminal renal disease: a radiologic controlled comparative study - Möst, Tobias; Jahn, Arne Eric; Heller, Katharina M.; Schiffer, Mario; Adler, Werner; Rohde, Maximilian; Weber, Manuel; Kesting, Marco Rainer; Lutz, Rainer (Oral Radiology, 2022)
Objectives The present radiological observational controlled study aims to evaluate the impact of secondary hyperparathyroidism (SHPT) due to chronic kidney disease (CKD) as well as the duration of dialysis on the mineralization of the mandible by standardized qualitative evaluation of digital panoramic radiographs. Methods Panoramic radiographs of CKD patients with SHPT and healthy controls were used for the qualitative analysis of the mandibular cortical index (MCI), the trabecular bone pattern (TBP), and calcification and resorption foci. Radiomorphometric indices were correlated to biochemical parameters and the duration of dialysis using the Spearman Rho test. Group comparisons were conducted using the Mann-Whitney U test and Fisher's exact test at a significance level of alpha <= 0.05. Interrater reliability of two physicians was estimated using Cohen's kappa. Results Inclusion and exclusion criteria were fulfilled by N = 41 patients. Statistically significant differences in the MCI (p < 0.001) as well as the TBP (p = 0.002) could be detected for the experimental group in comparison to the healthy control group. Focusing on calcification and resorption foci, no statistically significant difference could be detected between the groups (p = 0.244). The level of the detected parathyroid hormone (PTH) significantly correlated with TBP (Rho = 0.338; p = 0.031), while no significant relationship between TBP and the duration of the dialysis could be found. Conclusions Patients with SHPT due to CKD show statistically significant bone changes in the panoramic radiograph, whereby the grade of trabecular bone change correlates to PTH values.
CRIS-Team WoS Importer:2022-05-20